Calvin's Christology - Edmondson, Stephen (Cambridge books online., 2004)
Stephen Edmondson articulates a coherent Christology from Calvin's commentaries and his Institutes. What emerges is a picture of Christ as the Mediator of God's covenant through his threefold office of priest, king and prophet. This is the first significant volume to explore Calvin's Christology in several decades.